PENGARUH ASSET TANGIBILITY, CORPORATE TAX, PERTUMBUHAN PENJUALAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Liza Melya; Nurhalis Nurhalis (Departemen Manajemen, 2021)
This study aims to determine the effect of asset tangibility, corporate tax, sales growth, and profitability on capital structure in property and real estate companies listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 27 Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) from the 2016-2019 period. The analytical method used is panel data regression analysis using Eviews 10. Partially the results of the study show that asset tangibility, sales growth, and profitability have a negative and significant effect on capital structure, corporate tax has a positive and significant effect on capital structure on property companies and real estate in Indonesia. In this study, the variable asset tangibility, sales growth, and profitability are in line with the pecking order theory. While the variable corporate tax is in line with the trade-off theory.